Expulsion of iron-rich ferritin via CD63-mediated exosome drives ferroptosis resistance in ovarian cancer cells - Battaglia, Anna Martina; Sacco, Alessandro; Giorgio, Emanuele; Petriaggi, Lavinia; Elzanowska, Julia; Cruz, Ana Rita; Rocha, Luis; Pereira, Catarina Esteves; Strano Moraes, Maria Carolina; Palazzo, Luca; De Vitis, Claudia; Costa-Silva, Bruno; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionFerroptosis is a promising new target for ovarian cancer (OVCA) treatment. However, some OVCA cell types resist the induction of ferroptosis by limiting the intracellular accumulation of the labile iron pool (LIP).MethodsHEY, COV318 and PEO4 were treated with erastin and assessed for cell viability by using PI flow cytometry assays. Erastin-affected iron metabolism was analysed by using FerroOrange assay, Western Blot (WB) analysis of ferritin heavy chain (FtH), transferrin receptor (CD71), and ferroportin (FPN). Mitochondrial reactive oxygen species (mitROS) and lipid peroxidation were quantified via MitoSOX and BODIPY-C11 flow cytometry assays, respectively. Exosomes (EVs) were collected from cell culture media through ultracentrifugation and then enumerated and analyzed by Nanoparticale Tracking Analysis (NTA) and transmission electron microscopy (TEM). CD63 protein expression in EVs was measured through WB by using CD9 as a loading control. Loss-of-function assays for FtH and CD63 were performed by using siRNA-mediated transient transfection.ResultsWe demonstrate that erastin treatment (8 µM, 8 h) is accompanied by the release of iron-rich ferritin via EV pathway in COV318 and PEO4 OVCA cells, thus failing to exert cytotoxic effects. Mechanistically, erastin causes the upregulation of CD63, a tetraspanin involved in forming multivesicular bodies (MVBs) and EVs, and the increase of MBVs assessed by transmission electron microscopy. Consistent with these findings, EV isolation followed by nanoparticle tracking analysis revealed a significant increase in EVs/cell in erastin-treated COV318 and PEO4 cells. Notably, EVs harvested from these cells contained CD63 and FtH, a major iron-storage protein. Inhibition of EV biogenesis with GW4869 prevented FtH release and restored LIP accumulation, lipid peroxidation, and ferroptosis sensitivity in COV318 and PEO4 cells.DiscussionOverall, our results indicate that OVCA cells can utilize CD63+ EVs to secrete iron-rich ferritin as a mechanism to evade erastin-induced ferroptosis. These findings suggest that combining erastin with EV inhibitors could offer promising strategy for overcoming ferroptosis resistance in OVCA.